Comprehensive analysis of EGFR T790M detection by ddPCR and ARMS-PCR and the effect of mutant abundance on the efficacy of osimertinib in NSCLC patients - Li, Yue; Xu, Yuxia; Wu, Xiaoyan; He, Caiyun; Liu, Qing; Wang, Fang (Journal of Thoracic Disease, 2019)
Background: Patients with non-small cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations often develop systemic disease progression during treatment with EGFR-tyrosine kinase inhibitors (TKIs). Droplet digital polymerase chain reaction (ddPCR) and amplification refractory mutation system (ARMS)-PCR are routinely applied for detection of EGFR mutations, including T790M, which is associated with TKI sensitivity. We compared the efficiency of ddPCR and ARMS-PCR in detecting T790M and explored the association between T790M abundance and osimertinib efficacy. Methods: Genomic DNA (gDNA) from tissue and cells in hydrothorax and circulating tumor DNA (ctDNA) from peripheral blood (PB), and clinicopathological data were retrospectively collected from 263 patients who visited Sun Yat-sen University Cancer Center for T790M test. Results: Mean T790M abundance and mutant copy number of cases tested positive by both methods, i.e., the ddPCR+ARMS+ group (19.1%, 636.9), were higher than those in the ddPCR+ARMS− group (0.36%, 12.1), suggesting that ddPCR is more sensitive in detecting samples with low mutant abundance than ARMS-PCR. T790M detection rate was comparable for gDNA and ctDNA samples (44.7% vs. 37.6%, P=0.242); however, gDNA sample tended to show more T790M abundance in ddPCR analysis. T790M coexisted with L858R mutation (8/11) more than with deletions in exon 19 (19del) mutation (3/11) in TKI-naive tumors, while 19del co-occurred as often as L858R in post-TKI tumors. T790M+ patients benefited more from osimertinib and showed longer progression-free survival (PFS) (not achieved vs. 10.1 months, P=0.0399), while lower T790M abundance (